Issues of determining the legal status and liability of online tourism platforms in the Republic of Kazakhstan - Turysbek, A.B.; Beisov, Ye.Zh.; Issayeva, Zh.A. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
This article is devoted to the issues of determining the legal status of online tourism platforms and establishing the civil liability of platform operators in the context of the development of digital tourism in the Republic of Kazakhstan. The widespread introduction of digital technologies into the tourism sector has fundamentally transformed the methods of providing tourism services and has led to the formation of new models of relations among tourists, tourism service providers, and online platforms. Despite the rapid expansion of online tourism services, the existing national legislation does not yet provide a clear and consistent regulatory framework for the legal relations arising from the operation of online tourism platforms. This study examines the legal status of online tourism platforms within the digital tourism environment, clarifies their role in tourism-related legal relations, and evaluates how effectively the legislation of the Republic of Kazakhstan in the fields of tourism regulation, civil law, and consumer protection responds to the practical issues associated with their functioning. The research employs formal-legal, comparative-legal, and doctrinal methods of analysis, and examines national and foreign scholarly approaches as well as international experience. The article substantiates that a unilateral classification of online tourism platforms solely as information intermediaries or as tourism service providers is insufficient. The research findings demonstrate that such platforms exert a significant influence on the conclusion of tourism transactions, tourists’ freedom of choice, and the formation of service terms and conditions. Moreover, the absence of a clearly defined legal status of online tourism platforms, as well as the uncertainty regarding the scope of their liability towards tourists, directly affects the level of protection of tourists’ rights and complicates the resolution of disputes in practice. The conclusions of the study justify the need to improve the legal regulation of digital tourism and offer scientifically and practically significant propositions aimed at defining the independent legal status of online tourism platforms and clarifying the scope of their liability.